Explanation of Production Room Workers' Complaints Regarding Noise Exposure Below the NAB in Furniture Production Rooms - Helina Helmy; Lutfiah Dwi Sanrani (International Journal of Health and Pharmaceutical (IJHP), 2025)
The wooden furniture industry is a growing informal sector in Sukarame District, Bandar Lampung City, characterized by a work environment filled with exposure to physical factors such as noise. Although noise levels in some production areas are still below the Threshold Limit Value (TLV) of 85 dBA, workers continue to report health complaints related to this exposure. This study aims to explain complaints of production area workers regarding noise exposure that is still below the TLV. The method used is a qualitative descriptive study of 15 workers from three wooden furniture industries and direct observation of the work environment. The results showed that most workers experienced complaints such as headaches, difficulty concentrating, fatigue, and sleep disorders. These complaints were associated with long working hours, the type of machinery used, and the failure to use personal protective equipment (PPE) such as earplugs. Although noise levels have not exceeded the TLV, continuous exposure for 8 hours or more per day still has a psychophysiological impact on workers. Interventions such as work time management, education on the use of PPE, and machine maintenance are needed to reduce noise intensity. These findings emphasize the importance of evaluating noise risks not only based on threshold values, but also taking into account workers' perceptions and subjective health conditions.